Biologically inspired QoS aware routing protocol to optimize lifetime in Sensor Networks - Archana, S.; Saravanan, N. P. (2014 International Conference on Recent Trends in Information Technology, 2014)
A Wireless Sensor Network (WSN) is a self-governing network of sensor nodes organized in autonomous manner to monitor the region; connected using wireless links. Each node communicates with the other neighbor nodes, which lie in its transmission range and the entire region monitored by the combined effort of all the sensor nodes in the network, are termed as coverage area. The purpose of sensor nodes is to convey the event occurred to the base station or the sink node. Due to dynamic topology and limited network resources, sensor nodes experience a high failure rate. The ant based enhanced BiO4SeL QoS aware routing algorithm (EBiO4SeL) designed is based on the meta-heuristic approach of Ant Colony Optimization (ACO) framework, stimulated by natural ant behavior. Artificial ants are used to gather the QoS parameters such as delay, bandwidth, bit error rate, energy, signal strength etc., of the neighbor nodes. The path chosen for data transfer is computed with Path Preference Probability which satisfies all the Quality of Service (QoS) requirements. This algorithm is suitable for real time applications as it enhances node lifetime and downgrades packet loss and end to end delay. It is compared with existing BiO4SeL (Biologically-inspired Optimization for Sensor Lifetime) routing protocol.